Signet Ring Cell Carcinoma of the Colon Radiologically Stimulating Ileocecal Tuberculosis. (1st December 1992) - Kwan, WC Peter; Freeman, HJ
Abstract : A 65-year-old East Indian woman with episodic vomiting and anemia had radiological evaluations showing calcified lymph nodes in the abdomen and chest, with narrowing of the ileocecal valve and ascending colon suggesting the possibility of ileoccal tuberculosis. Evaluations subsequently proved this to be a signet ring cell carcinoma of the colon with infiltration of the terminal ileum.